Stir bar sorptive extraction and gas chromatography : mass spectrometry for the analysis of biological matrices - Stopforth, A. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2007.